Diversity and distribution of plant parasitic-nematodes on golf courses in localities of Baja California Sur, Mexico - Sánchez-Arce, Omar Jorge; Palacios-Espinosa, Alejandro; Carillo-Fasio, José Armando; Hernández-Montiel, Luis Guillermo; Mirella Romero-Bastidas, Mirella (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Golf is a tourist attraction in Baja California Sur (BCS), Mexico. However, the quality of its fields is detracted by presenting yellowing and death on tufgrass. Plant parasitic nematodes are one of the main limitations around the world. However, in BCS, its presence is unknown. In order to determine the diversity and distribution of phytonmatodes in golf courses in BCS, soil samples were collected in four courses. Nematode extraction was done using the Baerman funnel technique. Specimens were identified at the genus level and the population in each zone was quantified. The genera Meloidogyne, Helicotylenchus, Criconema, Xiphinema, Pratylenchus, Tylenchus, Hoplolaimus and Trichodorus were associated with the death of tufgrass with significant variations (p<0.05) in populations. These results are the first records of these genera in the golf courses evaluated, useful in the development of in the State.